Implementation of industrial complex and port of pecÃm and its consequences on the development of local municipality SÃo GonÃalo do Amarante - Cristiane EleutÃrio Carvalho DeusdarÃ (2013)
This study aims to analyze the development of SÃo GonÃalo do Amarante due to the implementation of Industrial and Port Complex of PecÃm. Initially, it is made an approach at a conceptual level of Local Economic Development, highlighting some important aspects related to this subject. It should be noted that local government has an important role in the development process getting, excessively, practicable solutions to the socioeconomic problems of the community in search of partnerships between the public and private sectors and society. In this perspective, we seek to show clearly that the decision to build a new enterprise of the size of Industrial and Port Complex of PecÃm brought significant impacts to the development of the Municipal District of SÃo GonÃalo do Amarante. The specific reference of this work derives in function of harbour and the largest part of Industrial Complex are located in that territorial area. Finally, this dissertation seeks to highlight, at the light of facts and data, the resultant reflexes from such an enterprise in that municipality.